2019
DOI: 10.1055/a-0977-2667
|View full text |Cite
|
Sign up to set email alerts
|

Overestimation of Risk and Increased Fear of Long-term Complications of Diabetes in People with Type 1 and 2 Diabetes

Abstract: Objective The quality report of the disease management programmes of North Rhine Westphalia 2016 showed prevalences for long-term complications (neuropathy, nephropathy, retinopathy) of less than 30% for people with diabetes type 1 (DM1) and type 2 (DM2). The aim of this study was to assess risk expectations and fear regarding long-term complications of diabetes in people with DM1 and DM2. Methods We assessed risk expectations and fear regarding diabetes complications in people with DM1 (n=110) and DM2 (n=143 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 15 publications
0
16
0
2
Order By: Relevance
“…Our study found that fear of health complications was a motivator for DSM. Past studies also reported patients’ fear of health complications as the main reason for managing their diabetes (Arend et al, 2019; Kuniss et al, 2019; Wukich et al, 2018). Patients feared not only health complications but also the impact of these complications or their death on their families’ fate.…”
Section: Discussionmentioning
confidence: 99%
“…Our study found that fear of health complications was a motivator for DSM. Past studies also reported patients’ fear of health complications as the main reason for managing their diabetes (Arend et al, 2019; Kuniss et al, 2019; Wukich et al, 2018). Patients feared not only health complications but also the impact of these complications or their death on their families’ fate.…”
Section: Discussionmentioning
confidence: 99%
“…Health care providers should explore the reason for this with the patient. Is the patient actually eating healthily due to diabetes-related worries which are common in diabetes and can result in poor adherence to diabetes self-care in the long term, 21 , 22 or does the patient use the diagnosis as a personal driver for making healthy self-management decisions? 23 , 24 …”
Section: Discussionmentioning
confidence: 99%
“…Health care providers should explore the reason for this with the patient. Is the patient actually eating healthily due to diabetes-related worries which are common in diabetes and can result in poor adherence to diabetes self-care in the long term, 21,22 or does the patient use the diagnosis as a personal driver for making healthy self-management decisions? 23,24 We examined diet quality in relation to self-perceived diet healthiness and found that diet quality was higher among self-perceived healthy eaters compared with less healthy eaters based on higher intakes of vegetables, fruit, fish, fibre and protein both in T1D and T2D respectively, and additionally a lower sugar intake in the T1D group.…”
mentioning
confidence: 99%
“…Thus, about 20%–40% of PWD may experience clinically relevant FDC. Some studies suggest higher FDC levels in persons with established diabetes complications (Arend et al, 2019; Taylor et al, 2005), which would appear reasonable, but there are also inconsistent findings (Kuniss et al, 2019).…”
Section: Current Evidencementioning
confidence: 99%